2012
DOI: 10.1007/s00359-012-0755-9
|View full text |Cite
|
Sign up to set email alerts
|

Corneal microprojections in coleoid cephalopods

Abstract: The cornea is the first optical element in the path of light entering the eye, playing a role in image formation and protection. Corneas of vertebrate simple camera-type eyes possess microprojections on the outer surface in the form of microridges, microvilli, and microplicae. Corneas of invertebrates, which have simple or compound eyes, or both, may be featureless or may possess microprojections in the form of nipples. It was previously unknown whether cephalopods (invertebrates with camera-type eyes like ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Microprojections are also found on the epithelium of the cornea, intestines, and kidney glomerular [10][12]. The structure and function of microprojections in other epithelial tissues has been well described.…”
Section: Introductionmentioning
confidence: 96%
“…Microprojections are also found on the epithelium of the cornea, intestines, and kidney glomerular [10][12]. The structure and function of microprojections in other epithelial tissues has been well described.…”
Section: Introductionmentioning
confidence: 96%
“…Earlier anatomical studies revealed that the outer surface of the cornea of zebrafish (Danio rerio) is covered with nanowrinkles . Similar nanotopographies but of different geometries were also observed on the corneal tissue of other vertebrates, such as mammals, including humans, fishes, ,,, and even invertebrates such as cephalopods . Possible functions of these surface features include tear film stability, , antireflectivity, and nutrient and gas interchange .…”
Section: Introductionmentioning
confidence: 71%
“…19 Similar nanotopographies but of different geometries were also observed on the corneal tissue of other vertebrates, 20−22 such as mammals, 20 including humans, 23 fishes, 19,21,22,24 and even invertebrates such as cephalopods. 25 Possible functions of these surface features include tear film stability, 20,23 antireflectivity, 25 and nutrient and gas interchange. 22 Here, we propose a hypothesis that these nanowrinkles help resist fouling while preserving the optical transparency of the tissue.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In addition to its effect on the lipid layer, studies have observed that it exerted cytotoxic effects on epithelial cells and the microvilli of the corneal apical epithelial cells. 32 The microvilli increase the ocular surface area for tear adherence, 33 the quality of these surfaces being an important determinant of tear film stability since the tear film is anchored to them.…”
Section: Discussionmentioning
confidence: 99%